Best Answer

Expressed as a surd in its simplest form, sqrt(234) = 3 sqrt(26).

Q: What is the simplified form of sqrt 234?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

sqrt(234) = 3*sqrt(26).

sqrt(300n11) = sqrt(100n10*3n) = sqrt(100n10)*Sqrt(3n) = 10n5*sqrt(3n)

sqrt(305) = sqrt(5)*sqrt(61) which cannot be simplified further.

Expressed as a surd in its simplest form, sqrt(245) is equal to 7 sqrt(5).

3 sqrt (3)Put the radical where the "sqrt" is with the second 3 inside.

Related questions

sqrt(234) = 3*sqrt(26).

sqrt(300n11) = sqrt(100n10*3n) = sqrt(100n10)*Sqrt(3n) = 10n5*sqrt(3n)

sqrt(51) cannot be simplified.

sqrt(72) = sqrt(36*2) = sqrt(36)*sqrt(2) = 6*sqrt(2).

sqrt(360) = 6*sqrt(10)

It is + or - 2*sqrt(24).

sqrt(305) = sqrt(5)*sqrt(61) which cannot be simplified further.

Expressed as a surd in its simplest form, sqrt(384) = 8 sqrt(6).

sqrt(45y12) = sqrt(5*9y12) = sqrt(5)*sqrt(9y12) = sqrt(5)*3y6

Expressed as a surd in its simplest form, sqrt(245) is equal to 7 sqrt(5).

sqrt(30) cannot really be simplified. You could write it as sqrt(2)*sqrt(3)*sqrt(5) but that is not simplification!

3 sqrt (3)Put the radical where the "sqrt" is with the second 3 inside.